Everyday Applied Geophysics 2 : Magnetics and Electromagnetism - Florsch, Nicolas, author 648615; Muhlach, Frédéric, author 648616; Kammenthaler, Michel, author 648617; ScienceDirect (Online service) 7722 (London : Elsevier, 2018)
Everyday Applied Geophysics 2: Electromagnetics and Magnetics covers the physical methods permitting the environmental exploration of the sub-surface in 1, 2, 3 or 4 dimensions (the latter for time-lapse in terms of physical environmental state and geometry). The book specifically addresses the feasible methods that are accessible and affordable to all users, providing a simple apparatus of electronic diagrams and free, Internet open-source software links for data interpretation.